2000
DOI: 10.1080/00480169.2000.36176
|View full text |Cite
|
Sign up to set email alerts
|

Splenic mast cell tumour and mastocytaemia in a cat: case study and literature review

Abstract: Splenectomy and treatment with corticosteroids appears to have resulted in remission of clinical signs and anaemia. A reduction in the concentration of mast cells in the peripheral blood had not occurred 6 weeks postsplenectomy, but was evident by 10 months post-splenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 12 publications
2
22
1
Order By: Relevance
“…Splenic MCT is mainly a disease of older cats with no breed or sex predilection. The median age of cats in this study was 13 years, which is consistent with previously reported data . Additionally, most of the cats in this study were domestic breeds and males and females were equally distributed.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Splenic MCT is mainly a disease of older cats with no breed or sex predilection. The median age of cats in this study was 13 years, which is consistent with previously reported data . Additionally, most of the cats in this study were domestic breeds and males and females were equally distributed.…”
Section: Discussionsupporting
confidence: 91%
“…Splenic mast cell neoplasia is one of the most common splenic tumors in the cat, representing 15%‐27% of all splenic diseases in this species . Older cats are most often affected, with a mean age of 9‐13 years, and no breed or sex predilection has been reported …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mouse anti-human tryptase antibody has been used to detect mast cells in the small intestine from camels, 4 mast cell subtypes have not been adequately evaluated. Erythrophagocytosis and vacuolation in the mast cells noted in the current case have been reported 2,9,15 in both neoplastic and normal mast cells from several species, but the significance of this finding is unclear. According to the findings in the present case, it is also noteworthy that this antibody against KIT exhibits cross-reactivity with llama KIT and can be used to identify mast cells in this species.…”
mentioning
confidence: 62%
“…17 In cats, the only reported round cell neoplasia exhibiting erythrophagocytosis, to our knowledge, is mast cell disease. [18][19][20][21] The marked erythrophagocytosis by neoplastic T cells in this case is of clinical interest because this cat presented with a significant nonregenerative anemia and subsequent lethargy and weight loss.…”
Section: Discussionmentioning
confidence: 99%